The Truth of Cultural Diplomacy - Riski Muhamad Baskoro (AEGIS : Journal of International Relations, 2020)
Since the United States Information Agency (USIA) is no longer active to operate cultural diplomacy in the post-cold war, the concept of cultural diplomacy has experienced a time of crisis in the context of International Relations studies. For a decade, cultural diplomacy was marginalized and considered obsolete until finally in the early 2000s, cultural diplomacy was revived and activated both in practice and theory. Since then, cultural diplomacy has returned to its path. The discourse of cultural diplomacy in International Relations studies has developed to gain more specific activities. This is a qualitative research, with the aim of understanding cultural diplomacy in a more holistic way. The results of this study indicate a debate and a lack of consensus on several aspects of cultural diplomacy and bringing much unclear explanation.  This study also shows a dichotomy between cultural diplomacy and other approaches.